The Effects of Different Scoring Systems on Upset Percentage and Match Length in Tennis: A Simulation Study - Harris, Sean (Journal of Sports Research, 2016)
Tennis has used many different scoring systems throughout its history. Researchers have been examining these scoring systems for over forty years. While several intuitive themes have emerged, no systematic examination on how different scoring systems affect the stronger player’s probability of winning over a range of serving strengths has been done. This research study used simulation to examine the three most common scoring systems used in the United States and their effect on match win probability, total points played, and expected length of the match. Moving from ad to no ad or 10-point scoring can result in a more than 3.5% and 5% respective decrease in the probability of the stronger player winning a match. When applied to NCAA Division I team tennis, moving from ad to no ad can decrease the stronger team’s probability of winning by over 4%. Changes between scoring systems are more pronounced at relatively weaker serving strengths.